Multimorphic Materials: Spatially Tailoring Mechanical Properties via Selective Initiation of Interpenetrating Polymer Networks. Issue 9 (30th December 2022) - Allen, Marshall J.; Lien, Hsu‐Ming; Prine, Nathaniel; Burns, Carter; Rylski, Adrian K.; Gu, Xiaodan; Cox, Lewis M.; Mangolini, Filippo; Freeman, Benny D.; Page, Zachariah A.
Abstract: Access to multimaterial polymers with spatially localized properties and robust interfaces is anticipated to enable new capabilities in soft robotics, such as smooth actuation for advanced medical and manufacturing technologies. Here, orthogonal initiation is used to create interpenetrating polymer networks (IPNs) with spatial control over morphology and mechanical properties. Base catalyzes the formation of a stiff and strong polyurethane, while blue LEDs initiate the formation of a soft and elastic polyacrylate. IPN morphology is controlled by when the LED is turned "on", with large phase separation occurring for short time delays (≈1–2 min) and a mixed morphology for longer time delays (>5 min), which is supported by dynamic mechanical analysis, small angle X‐ray scattering, and atomic force microscopy. Through tailoring morphology, tensile moduli and fracture toughness can be tuned across ≈1–2 orders of magnitude. Moreover, a simple spring model is used to explain the observed mechanical behavior. Photopatterning produces "multimorphic" materials, where morphology is spatially localized with fine precision (<100 µm), while maintaining a uniform chemical composition throughout to mitigate interfacial failure. As a final demonstration, the fabrication of hinges represents a possible use case for multimorphic materials in soft robotics. Abstract : Two disparate polymer networks are created simultaneously using non‐interacting chemical reactions and light as a stimulus. Upon turning the light on, the polymers want to phase‐separate like oil and water, but the process is hindered as they interlock. Thus, the degree and location of phase separation, and in‐turn mechanical properties, can be precisely controlled by the "flick of a switch".